Chitosan as a Capping Agent of Silver Nanoparticles - Badi'ah, Hanim Istatik (Indonesian Journal of Chemical Research, 2021)
Silver nanoparticles have been developed in many applications because of their optical and reactivity properties. One of the disadvantages of silver nanoparticles is their low level of stability because their surface is easy to aggregate. It is necessary to have other materials such as chitosan as a capping agent on the surface of silver nanoparticles to prevent aggregation. This study aimed to determine the ability of chitosan as a capping agent for silver nanoparticles. The ability of chitosan was evaluated based on the stability test and characterization using a UV-Vis, PSA, and FTIR spectrophotometer. The silver nanoparticles formed producing a yellow color with a wavelength of 401 nm and a size of 13.48 nm. The volume of chitosan that gave optimal results in stabilizing silver nanoparticles was 2.0 mL.